Language Learning or Language Education? Reviving Teachers’ Moral Exemplary Function - Aris Kurniawan; Yazid Bastomi (Pascasarjana UM, 2017)
Abstract: English teaching is not only simply devoted to make students to master language contents. More than that, teachers may infuse moral values like politeness, respect, and honesty during the teaching and learning process. This preliminary case study explored teacher’s perception to their moral exemplary function and how they play their role as a moral agent in the classroom. Through interviews with two English teachers, it is revealed that teachers regard the exemplary function is crucial for students’ moral development. Teachers could actualize their role as moral model by showing good attitude in speaking and behave properly in front of students.Key Words: character building, English language teaching, role model Abstrak: Pembelajaran bahasa Ingris tidak sesederhana mengajarkan konten bahasa kepada siswa. Lebih dari tu, seorang guru bahasa inggris seharusnya juga menyampaikan nilai moral yang melandasai penggunaan bahasa seperti norma kesopanan, menghargai, dan juga kejujuran. Penelitian studi kasus ini bertujuan untuk memahami persepsi guru bahasa inggris tentang peluang mereka menjadi menjadi teladan bagi siswa dan bagaimana guru mencontohkan nilai moral kepada siswa. Dari data interview, diketahui jika guru meganggap bahwa dengan menjadi contoh yang baik, mereka bisa mendorong pembentukan karakter siswa. Bukan hanya ucapan, sikap dan tingkah laku adalah dua hal penting untuk bisa mewujudkan peran guru sebagai teladan bagi siswa.Kata kunci: pendidikan karakter, pembelajaran bahasa, role model